Assessing Urban Yellow Fever Transmission Risk: Aedes aegypti Vector Competence in Argentina - Estefanía R. Boaglio; Evangelina Muttis; Mariel Feroci; Cintia Fabbri; Graciela Minardi; Juliana Sánchez; María V. Micieli; Silvina Goenaga (Viruses)
Yellow fever is a viral disease with historical importance since epidemics caused thousands of deaths at the end of the 19th century in Argentina. That event was associated with the presence of Aedes aegypti. After the mosquito eradication in South America in the 1960–1970 decade, no epidemic was detected related to this species but epizootics have occurred due to sylvatic vectors belonging to Haemagogus and Sabethes genera. Due to the recolonization of Ae. aegypti and its expanded distribution, the risk of the urbanization of yellow fever has increased over time. However, the reasons why the urban cycle of the yellow fever virus (YFV) has not occurred in South America so far are unknown. We explore the vector competence of Ae. aegypti for YFV transmission. The mosquitos evaluated belonged to colonies from center and northwest cities from Argentina, taking into account the particular genetic features of this mosquito species detected in this country from 2016. We used a viral strain originally isolated in 2009 from Sabethes albiprivus in the country. Viral infection in mosquito body, legs, and saliva was evaluated to estimate the rates of infection, dissemination, and transmission. Our results indicate that both mosquito colonies are competent vectors in the transmission of the YFV but with differences between them. Regarding the infection timeline, we observed a very early infection in the La Plata colony at 3 DPI in contrast to previous studies. This research improves our understanding of the risks of urban YFV transmission in Argentina, highlighting the need for surveillance and specialized vector control strategies in urban settings to prevent yellow fever outbreaks.